The Role of Environmental Factors on Sleep Patterns and School Performance in Adolescents - Dimitriou, Dagmara; Le Cornu Knight, Frances; Milton, Patrick (Frontiers in Psychology, 2015)
Background. Modern life, with its many distractions, is seeing sleep quantity and quality decline during adolescence. This is a concern as research persuasively demonstrates the negative impact of reduced sleep on academic achievement, both in terms of learning and behaviour. Aims. This study examined the relationship between sleep and school functioning in adolescence, with a focus on environmental factors that might mediate this relationship. Sample and method. Forty-seven adolescents took part. Sleep was measured using the School Sleep Habits Survey and a sleep diary. School records of year grade point averages provided a measure of academic achievement. Raven’s Standard Progressive Matrices gave a measure of general cognitive processing. Environmental sleep factors falling into three groups, namely, stimulant consumption, media use and exercise, were measured using a self-report questionnaire. Results. An average of 7.08 hours of sleep was reported. Correlations revealed that Total sleep time (TST) and bedtimes on weekdays were strongly associated with academic achievement. Morning/eveningness and sleep/wake behaviour problems had a strong relationship with performance on the Ravens. Stimulant consumption and media use before bed revealed strong relationships with TST and bedtimes on weekdays. Crucially, mediation analyses confirmed that both caffeine consumption and electronic media use before bedtime were negatively associated with academic performance, via the mediating pathway by affecting sleep. Exercise was not associated with any of the sleep variables, but was associated with better academic performance. Conclusion. The current findings highlight that, now more than ever, parents, schools and policy makers must be aware of the negative effects of caffeinated substances marketed to students, and electronic media use on their sleep habits. Our findings suggest that targeting caffeine consumption and electronic media use before bed may represent effective routes in alleviating modern teenage sleep debt, and in turn enhancing academic performance.